John Keats, Jane Taylor, and Poetic Ambition. - Pascoe, Judith (Romanticism, 2024)
In an 1817 letter, John Keats mentioned giving a copy of Jane Taylor's Essays in Rhyme, on Morals and Manners (1816) to his sister Fanny Keats. The reference to Jane Taylor hints at how and why Taylor captured Keats's interest. Keats acquired Taylor's book at a moment of peak aspiration when he was struggling to write his long, ambitious poem Endymion, and when he had switched publishers to Taylor and Hessey, the publisher of Jane Taylor and her mother Ann Martin Taylor. With a vision of himself as the publisher of major writers, John Taylor was able to gamble on Keats because the Taylors' books were steady sellers. This article argues that when Keats read Taylor's Essays in Rhyme, he read a work that met with a more favourable reception than did his own early work. This article further underscores that the commercial trajectories of the Taylors and Keats were intertwined. The profits from the Taylors' books served to underwrite the publishing of Keats's work.